2018
DOI: 10.1590/1806-9282.64.04.374
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of incidence, mortality and cost of nontraumatic abdominal emergencies treated in Brasil in a period of nine years

Abstract: Non-traumatic abdominal emergencies are extremely prevalent. Hence, the importance of having updated and comparative data on the mortality rate, number of hospitalization and cost generated by these diseases to provide better healthcare services in public hospitals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 8 publications
0
6
0
1
Order By: Relevance
“…Although incidence of all 10 overlapping studies were reported alongside all other studies in the tables, only 4 were included in the meta-analyses and figures. 3,[30][31][32] In total, 44 studies, from the following regions, met our inclusion criteria: Europe (n ¼ 24 10,12,13, ), North America (n ¼ 11 3,4,9,[27][28][29][30][31][53][54][55] ), South America (n ¼ 1 56 ), Asia (n ¼ 5 [57][58][59][60][61] ), and Oceania (n ¼ 3 [62][63][64] ). The 4 studies reporting the incidence of acute pancreatitis in children exclusively were North America (n ¼ 2 54,55 ), Asia (n ¼ 1 57 ), and Oceania (n ¼ 1 63 ).…”
Section: Resultsmentioning
confidence: 99%
“…Although incidence of all 10 overlapping studies were reported alongside all other studies in the tables, only 4 were included in the meta-analyses and figures. 3,[30][31][32] In total, 44 studies, from the following regions, met our inclusion criteria: Europe (n ¼ 24 10,12,13, ), North America (n ¼ 11 3,4,9,[27][28][29][30][31][53][54][55] ), South America (n ¼ 1 56 ), Asia (n ¼ 5 [57][58][59][60][61] ), and Oceania (n ¼ 3 [62][63][64] ). The 4 studies reporting the incidence of acute pancreatitis in children exclusively were North America (n ¼ 2 54,55 ), Asia (n ¼ 1 57 ), and Oceania (n ¼ 1 63 ).…”
Section: Resultsmentioning
confidence: 99%
“…The authors have noted an increase in the frequency of acute appendicitis, AP and acute diverticulitis over the years. Mortality due to complications of gastroduodenal ulcers, acute diverticulitis and AP was higher when compared to other causes of AA 18 .…”
Section: Introductionmentioning
confidence: 80%
“…One recent Brazilian study has evaluated the incidence and mortality of patients with AA admitted to the hospital through the Brazilian Unified Public Health System (SUS) 18 , 22 . The most common causes were CC, acute appendicitis, AP, complications of gastric and duodenal ulcers, acute diverticulitis and inflammatory bowel disease (B),(C).…”
Section: Introductionmentioning
confidence: 99%
“…Diversos estudos procuraram relacionar taxas de mortalidade com determinadas condições e agravos de saúde (AMARAL et al, 2018;AQUINO et al, 2018;LEMOS;ALEM;CAMPOS, 2018;SIMÕES et al, 2018 CAVALCANTE et al, 2018;CITRON et al, 2018;DAVID;NASCIMENTO, 2018;SCOTTA et al, 2018;KUPEK, 2018;BESSA;BONATTO, 2019;NASCIMENTO, 2019). Mas em geral, todos os estudos relacionaram duas ou mais unidades de análise provenientes do DATASUS em um determinado período de tempo.…”
Section: Estratégias De Pesquisaunclassified